2004
DOI: 10.1158/0008-5472.can-03-1675
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-Binding Protein 3 Induces Caspase-Dependent Apoptosis through a Death Receptor-Mediated Pathway in MCF-7 Human Breast Cancer Cells

Abstract: Insulin-like growth factor-binding protein (IGFBP)-3 has been shown to potently inhibit cell proliferation in various cell systems. However, the specific mechanisms involved in the antiproliferative action of IGFBP-3 have yet to be elucidated. In the present study, we demonstrate that IGFBP-3 induces apoptosis in an insulin-like growth factor (IGF)-independent manner through the activation of caspases involved in a death receptor-mediated pathway in MCF-7 human breast cancer cells. Induction of IGFBP-3 using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 64 publications
7
68
1
1
Order By: Relevance
“…In a study, Koyama et al (2010) investigated the relationship between pomegranate-induced apoptosis in human prostate cancer cells and the insuline-like growth factor (IGF)/IGF binding protein (IGFBP) system, as the IGF axis is critical for the regulation of apoptosis in many human cancer cell lines and IGFBPs in serum are responsible for regulation of IGF action, inhibition of cell proliferation and enhancement of apoptosis in many cell types, including prostate (Rajah et al, 1997) and breast (Gucev et al, 1996;Kim et al, 2004) cancers. They concluded that there are novel interactions between the IGF system and pomegranateinduced apoptosis, and pomegranate products modulate the tumor production and responsiveness to IGFs and the IGFBPs.…”
Section: Prevention Of Prostate Cancermentioning
confidence: 99%
“…In a study, Koyama et al (2010) investigated the relationship between pomegranate-induced apoptosis in human prostate cancer cells and the insuline-like growth factor (IGF)/IGF binding protein (IGFBP) system, as the IGF axis is critical for the regulation of apoptosis in many human cancer cell lines and IGFBPs in serum are responsible for regulation of IGF action, inhibition of cell proliferation and enhancement of apoptosis in many cell types, including prostate (Rajah et al, 1997) and breast (Gucev et al, 1996;Kim et al, 2004) cancers. They concluded that there are novel interactions between the IGF system and pomegranateinduced apoptosis, and pomegranate products modulate the tumor production and responsiveness to IGFs and the IGFBPs.…”
Section: Prevention Of Prostate Cancermentioning
confidence: 99%
“…DNA fragmentation is a marker and characteristic event of apoptosis (38). An ELISA-based assay performed with mouse monoclonal antibodies directed against DNA and histones provides a quantitative in vitro determination of histone-associated DNA fragments (38,39).…”
Section: ß-Elemene Sensitizes Nsclc Cells To Cisplatin-induced Cytotomentioning
confidence: 99%
“…7,8 Insulinlike growth factors (IGFs)-I and -II are structurally related polypeptides, which play an important role in cellular proliferation, differentiation and apoptosis. 9,10 They are regulated by a family of binding proteins (IGFBPs), of which six have been identified. 11 The IGFBPs modulate the biological action of IGF-I and IGF-II.…”
Section: Introductionmentioning
confidence: 99%